Pengelolaan Arsip Inaktif di Kantor Urusan Agama Kecamatan Karanganyar Kabupaten Kebumen - Titi Nur'aini Barokah; Dedeng Yusuf Maolani (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
This study aims to analyze the management of inactive archives carried out by KUA Karanganyar District, Kebumen Regency on the procedures for structuring and storing inactive archives of marriage certificates and inactive archives of waqf land and this research is expected to be used as an evaluation material for the management of inactive archives, both in KUA Karanganyar District, as well as in other KUA sub-districts in Indonesia. The method that the author uses is a type of descriptive research, a qualitative approach. Sources of data come from primary and secondary data. To support the research analysis, the researcher used the Pusposive Sampling technique. Data collection techniques used interviews, observations, documentation studies, and literature studies. Data analysis used the Miles and Huberman model, the steps consisted of data reduction, data presentation, drawing conclusions and verification. The results showed that the management of inactive archives of marriage certificates and inactive archives of waqf land in KUA, Karanganyar District, Kebumen Regency included structuring and storage activities. Each activity carried out has shortcomings and obstacles so that the management of inactive records is not in accordance with the standards of inactive records management.